2018
DOI: 10.1016/j.neuro.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic GABA levels and occupational manganese neurotoxicity: Association with exposure levels and brain MRI

Abstract: Excessive occupational exposure to Manganese (Mn) has been associated with clinical symptoms resembling idiopathic Parkinson's disease (IPD), impairing cognitive and motor functions. Several studies point towards an involvement of the brain neurotransmitter system in Mn intoxication, which is hypothesized to be disturbed prior to onset of symptoms. Edited Magnetic Resonance Spectroscopy (MRS) offers the unique possibility to measure γ-amminobutyric acid (GABA) and other neurometabolites in vivo non-invasively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 77 publications
(79 reference statements)
5
33
0
2
Order By: Relevance
“…To enhance the strength of the experiment, instead of measuring brain manganese levels using a part of the midbrain as performed for other assays in this study, we used a brain punching method to collect tissue from the caudate/putamen, globus pallidus, and substantia nigra (all subregions within the basal ganglia) and the thalamus. This was important because manganese is known to induce injury in the basal ganglia and the thalamus (2,3,37). We verified that SLC30A10 was expressed in these brain regions in WT mice (Fig.…”
Section: After Elevated Manganese Exposure Manganese Levels In Specisupporting
confidence: 65%
See 1 more Smart Citation
“…To enhance the strength of the experiment, instead of measuring brain manganese levels using a part of the midbrain as performed for other assays in this study, we used a brain punching method to collect tissue from the caudate/putamen, globus pallidus, and substantia nigra (all subregions within the basal ganglia) and the thalamus. This was important because manganese is known to induce injury in the basal ganglia and the thalamus (2,3,37). We verified that SLC30A10 was expressed in these brain regions in WT mice (Fig.…”
Section: After Elevated Manganese Exposure Manganese Levels In Specisupporting
confidence: 65%
“…Notably, the globus pallidus is particularly sensitive to manganese accumulation and induced injury (2,3). The thalamus is also a known manganese target (37). The reason why activity of SLC30A10 is critical to regulate manganese levels in these regions remains to be elucidated.…”
Section: Regulation Of Brain Manganese Homeostasis By Slc30a10mentioning
confidence: 99%
“…Using magnetic resonance imaging (MRI), several studies have shown significant brain accumulation of Mn in both humans and other animal models, are associated with increased risk of neurotoxicity. These subjects often show a characteristic accumulation of manganese in the basal ganglia, particularly in the globus pallidus (59)(60)(61). Mn accumulation was also observed in the frontal cortex ( Figure 1) (59).…”
Section: Routes Of Manganese Exposure and Accumulation In The Brainmentioning
confidence: 95%
“…These subjects often show a characteristic accumulation of manganese in the basal ganglia, particularly in the globus pallidus (59)(60)(61). Mn accumulation was also observed in the frontal cortex ( Figure 1) (59). While recovery upon cessation is possible (62), this rarely happens in cases of occupational exposures which are prolonged and cumulative.…”
Section: Routes Of Manganese Exposure and Accumulation In The Brainmentioning
confidence: 99%
“…Criswell et al (Criswell et al, 2018) used 6-[18F] fluoro-L-DOPA PET on Mn-exposed welders and workers and demonstrated lower caudate FDOPA uptake, indicating pre synaptic dopaminergic dysfunction in Mn-exposed subjects that was not associated with clinical parkinsonism. Magnetic Resonance Spectroscopy (MRS) was used to measure γ-amminobutyric acid (GABA), and thalamic GABA levels and motor function displayed a non-linear pattern of response to Mn exposure among welders, suggesting a threshold effect (Ma et al, 2018). Striatal and thalamic GABA did not differ between Mn-exposed workers, Parkinsonian patients or hemochromatosis patients, and controls (Casjens et al, 2018).…”
Section: Scientific Advances Reported At the Conferencementioning
confidence: 99%